Pengaruh Penggunaan Multi-Platform Akuntansi terhadap Ketepatan Waktu dan Akurasi Pelaporan Keuangan: Studi pada Perusahaan PT XYZ - Rachman, Daud Sofyan; Sulisyowati, Erna (Jurnal Riset Rumpun Ilmu Ekonomi, 2025)
This study aims to analyze the effect of using multi-platform accounting on the timeliness and accuracy of financial reporting at PT XYZ, a service company engaged in the distribution of cement. In carrying out its operations, this company uses three different types of accounting applications in the financial recording process, namely Microsoft Excel, Accurate and Semenku. This study uses a descriptive qualitative research method and data collection through observation. The results of the study indicate that the use of multiple platforms simultaneously can cause data inconsistencies and slow down the financial reporting process, but on the other hand it also provides flexibility in recording transactions. Therefore, system integration or evaluation of platform use is needed to improve the efficiency and accuracy of financial reporting.